'Information' and 'intelligence': The current divergences between national legal systems and the need for common (European) notions. Issue 3 (September 2017) - Cocq, Céline C.
The European Union (EU) has no powers to dictate to its Member States how to structure their criminal justice systems. But, it is a very good platform in which actors may think and work together in order to combat transnational crime by agreeing common legislation and actions. However, discrepancies remain with regard to definitions of key terms such as 'information' and 'intelligence' and also the distribution of competences between national authorities. These national discrepancies – highlighted by the analysis of a sample of EU Member States – lead to diverging methods and responses which may raise human rights issues and limit cross-border cooperation. A vertical and horizontal analysis, focusing on the definitions of the two terms provided in the different jurisdictions and on the way in which these definitions are influenced by the distributions of competences at the national level, calls for a more harmonized voice within the region.